Designing Interactive Videos in Online Multivariable Calculus Course to Support Student's Critical Thinking. Issue 1 (March 2021) - Firdaus, M; Mukhtar,; Darari, M B; Azis, Z
Abstract: Emphasizing critical thinking skills in the curriculum of higher education institutions is needed to produce graduates with higher order thinking skills. Given the importance of information technology for critical thinking in learning, it is necessary to understand the key factors related to learning designs that utilize information technology in their learning environment and consider the pedagogical and information technology alignment. This study aims to describe the process of analysing, designing, and developing interactive learning videos as part of the redesign of the multivariable calculus course to support students' critical thinking skills. This paper will describe the lessons learned from and the next steps in this research and development process.